Instrumentalizing pastoralism? Understanding hybrid tenure and governance in Ilkisongo Maasai land of southern Kenya - Unks, Ryan R. (Political geography, 2022)
Throughout Kenya, new governance regimes that are designed to sustain habitat connectivity for wildlife populations outside of national parks have gained increasing prominence. Though these new regimes often center a discursive emphasis on the synergies between wildlife conservation and pastoralist land use, it often remains unclear how they have interacted with colonial and post-colonial legacies that influenced pastoralists' relationships with land. As an effort to gain an improved understanding of the practices that conservation governance regimes deploy, and their underlying rationales, I present an empirically-driven account drawn from ethnographic field work in Kenyan Ilkisongo Maasai land surrounding Amboseli National Park. I argue that to understand recent configurations of land, it is essential to consider the multiple types of interlocking practices deployed by international wildlife conservation NGOs and the Kenyan state. Under a range of pressures to subdivide collectively titled land, a new territorial and governance configuration is emerging where land tenure will retain characteristics of being both private and collective. I argue that a discursive emphasis that frames conservation interventions as producing welfare for populations of wildlife and pastoralists alike has created new potentials to center the concerns of politically marginalized pastoralists, but has also raised risks of an ‘anti-politics’ that can reproduce and reinforce multiple dimensions of power asymmetries.